The Effect of Native and Pregelatinized Durian Seed Starch (Durio Zibethinus Murr) on The Dissolution Rate of Paracetamol Tablets - I Gusti Ngurah Agung Dewantara Putra (Jurnal Indonesia Sosial Sains, 2026)
Amylum is widely used as an excipient in pharmaceutical formulations, one of which is inert and can be mixed with any drug without causing a chemical reaction. The aim of this research is to know the preparation method of cassava amylum (Durio zibethinus, Murr) native and pregelatinized which is used as binder to dissolution rate of paracetamol tablet with granulation method. The native and pregelatinized amylum produced from cassava is carried out by a preliminary test to determine the nature of physical characteristics and to know the ability as a binder of the tablet. The paracetamol tablets produced from the two methods were tested dissolution using medium buffer phosphate at 37 ± 0,5 ° C (pH 5.8, 50 rpm). The results showed that cassava starch preparation method had an effect on dissolution rate of tablet. Pregelatinized amylum as binder on paracetamol tablet showed Q value (93,17 ± 0,01)% while native amylum showed value of Q (81,76 ± 0,20)%. The use of pregelatinized cassava starch as a binder on paracetamol tablet has better characteristic properties compared with native starch